Long-term affairs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Finding ways of sustaining interest in community initiatives is a question faced daily by thousands of groups involved in agricultural and rural development. Often, after an initial surge of activity and success, they find that energy drops,...